The Role of Report Texts in Improving Understanding of Chemical Material Through Practical Reports and Research in High Schools - Ndruru, Ester; Ardi, Mutiara; Sinaga, Sarah Agnesia; Lubis, Fitriani (CV. Rayyan Dwi Bharata, 2024)
This research aims to explore the effectiveness of using practicum reports in chemistry learning in high school, with a focus on developing students' writing skills and understanding of concepts. Formal education, as regulated in Law of the Republic of Indonesia no. 20 of 2003, has an important role in developing students' potential, including cognitive aspects and practical skills. The research method used is a combination of a qualitative approach through literature study and a quantitative approach through questionnaires filled out by students of SMAN 5 Medan. Data analysis showed that the majority of students (70%) agreed that the lab report enabled the application of chemistry concepts in hands-on practice, which improved their understanding. In addition, 90% of students felt motivated to explain the results of the practicum, and 85% felt happy with the practicum method used. The research results show that integration between practicum and report writing skills can increase students' understanding of chemistry concepts and interest in this subject. However, students' abilities in writing practical reports still need to be improved, especially in analyzing data and connecting theory with practical results. Thus, the use of practicum reports in chemistry learning in high school has proven to be effective in improving students' understanding and practical skills, although further efforts are still needed to improve students' analytical and scientific writing skills.